BARRIERS AND FACILITATORS TO PROVIDING COVID-19 CONTACT TRACING INFORMATION AMONG ADULT NIGERIANS - odikpo, Linda; Ayuba, Balas; Ubah, Chinenye; Mbadugha, Chisom; Ndubuisi-Okoroezi, Lovelyn; Ikechukwu-Okoroezi, Jennifer (African Journal of Infectious Diseases (AJID), 2025)
Background – Contact tracing information as one of the measures of COVID-19 control had been met with some barriers and facilitators. This study was set to identify barriers and facilitators to providing COVID-19 contact tracing information among adult Nigerians. Materials and Methods - The study was a prospective web-based cross-sectional descriptive design. Multi-stage sampling technique was used to select 1015 adult Nigerians within 18-70 years age band. Data were collected through Google forms and analyzed with the aids of Statistical Package for Social Sciences version 22. Results – The majority (91.1%) of the respondents indicated that they will provide contact tracing information if they were confirmed or suspected to have COVID-19. The most identified facilitator to providing Covid-19 contact tracing information by the majority (90.7%) of the participants was to help stop the spread of COVID-19. More than average (58.9%) of participants did not trust the authorities; this was the most identified barrier to providing COVID-19 contact tracing information. The intent to provide contact tracing information was significantly associated with being a healthcare professional (p = .007) and place of residence (p = .044). Conclusion- This study has identified facilitators and barriers to providing COVID-19 contact information. Despite the progress in management of COVID-19, the future is not predictive; therefore, providing contact tracing information will remain relevant in planning strategic and specific interventions for controlling infectious diseases. Government should make more effort to improve public trust on confidentiality of information and governance in general.